A clustering review of vegetation-indicating parameters in urban thermal environment studies towards various factors. (December 2022) - Zhang, Jian; Khoshbakht, Maryam; Liu, Jianlin; Gou, Zhonghua; Xiong, Jie; Jiang, Maoting
Abstract: People in outdoor areas suffer from more heat stress than indoors during warm seasons due to the lack of shelters or cooling facilities. This problem is pressing with urban heat island and continuous global warming. Researchers have explored various strategies for ameliorating thermal stress, coining the term 'outdoor thermal environment (OTE)' for this area of study. It has been found that the OTE is affected by vegetation and other factors (i.e., geometry) of a location. There have been many studies on vegetation, with these conducted at various levels and using different methods. Several parameters have been used to characterise vegetation and have been found to statistically correlate with many thermal indices (i.e., physiologically equivalent temperature, PET; universal thermal climate index, UTCI etc.). This article reports on a review of journal papers that investigated the climatic regulations of vegetation. In this study vegetation-indicating parameters were clustered according to the methods, scope, and thermal indices. Studies involving large scales preferred general indicators (e.g., NDVI, vegetation cover etc.) whereas specific, detailed parameters (e.g., crown sizes) were more frequently used in studies of micro levels. Outdoor thermal environment studies involving vegetation were mostly conducted in regions with high heat stress levels. Also, remote sensing and meteorological station observation were more frequently used in large-scale studies, while small-scale studies preferred simulation and field measurements. Their findings were expressed by the statistical correlation between vegetation parameters and thermal indices. For instance, NDVI, LAI, and crown size were negatively correlating with temperatures. The findings of this study help inform directions for future vegetation studies regarding outdoor thermal environment designs. Researchers would be clearer on selection methods and thermal indices regarding their targets and supporting tools. Highlights: A clustering of urban thermal environment studies involving vegetation. Vegetation-indicating parameters were clustered into four types for comparison. Large scale studies focused on general indices such as NVDI or vegetation cover. Future studies should consider parameters for vegetation on building roofs/facades.